Pengaruh Intellectual Capital, Ukuran Perusahaan, dan Leverage Terhadap Kinerja Keuangan - Suzan, Leny; Nur Aini, Hani (Jurnal Ilmiah Akuntansi Peradaban, 2023)
The financial performance of a company is expeted to be able to find weakness and streghts by using the information presented in the financial statements for various interested parties in making decisions. This study aims to determine the influence of intellectual capital, company size, and leverage on financial performance. This study used 258 observational data from basic and chemical industry sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The analysis methods used by this study are descriptive statistical test and panel data regression analysis. The results showed that simultaneously intellectual capital, company size, and leverage affect financial performance. Meanwhile, partially, intellectual capital and leverage affect financial performance and company size does not affect financial performance.